Projection of the number of amputations in diabetics: an aid for the planning of sustainable Portuguese health services - Carolino, Elisabete (2022)
Amputation is the loss (surgical or traumatic) of a segment of the body, applied in the event of an injury (traumatic, vascular, or other) that has irreparably affected the human being, causing functional limitation. Amputation also represents a considerable negative socio-economic impact for families and governments. Knowing the numbers, and establishing the prevalence and future trends in limb loss is important for health care planning and for the rational allocation of resources, as a response to the growing indicators of demand for prostheses and related services. Diabetes is known as one of the leading causes of morbidity and mortality worldwide. Portugal is the fourth country in the European Union with the highest incidence rate of diabetes, according to the IDF Atlas (International Diabetes Federation, 2021). In the Annual Report of the National Diabetes Observatory - 2019 Edition, it is estimated that in 2018 there will be between 605 and 618 new cases of diabetes per 100,000 inhabitants. Although diabetes prevalence data are updated annually in Portugal through the INSA - Médicos Sentinela, with the COVID-19 pandemic, it is estimated that at least 20,000 diabetics have not had access to the necessary conditions for an early diagnosis. Therefore, data from this period underestimate the prevalence rate of Diabetes. The prevalence of complications related to diabetes, namely diabetic foot, tends to increase with the increasing number of people with the pathology. Studies show that 1 in 7 diabetics will develop foot ulcers in their lifetime, which is a risk factor for amputation. Amputation is probably the most feared and recognized complication of diabetes. It is estimated that about 50% of amputations and ulcerations can be prevented by evaluating the foot, and degree of risk of ulceration, thus allowing the implementation of preventive strategies. The main objectives of this work are: i) quantify and characterize the amputations performed in Portugal from the year 2000 to the present; ii) Model, estimate and predict the number of amputations by etiology and by level for the future. This is a retrospective observational cross-sectional study, designed using the Hospital Morbidity Database (BDGDH), for episodes with amputations, provided by the Central Administration of the Health System, IP. (ACSS), supervised by the Ministry of Health. The data refer to hospitalizations related to amputations in public hospitals of the National Health Service (SNS) in the mainland, which occurred between 2000 and 2019. It includes the dependent variables, calendar year, age, district (place of birth), gender, etiology, and level of amputation. It consists of the 20 initial records of diagnoses and the respective procedures associated with each episode of hospital admission. The disease and procedure criteria were defined according to the International Statistical Classification of Diseases, Injuries and Causes of Death, in the 9th revision of 1975 (ICD-9), with the respective code limits. Annual trends were estimated through Poisson regression models as well as the future incidence rates, sex, and age group stratified. Incidence rate projections were adjusted to the distribution of the resident population in mainland Portugal, considering the Portuguese statistical projections (National Institute of Statistics - INE).